Cross‐European validation of the ItchyQoL in pruritic dermatoses. (25th September 2018) - Zeidler, C.; Steinke, S.; Riepe, C.; Bruland, P.; Soto‐Rey, I.; Storck, M.; Garcovich, S.; Blome, C.; Bobko, S.; Legat, F.J.; Potekaev, N.; Lvov, A.; et al.
Abstract: Background: Chronic pruritus (CP) is a frequently occurring symptom in inflammatory dermatoses, causing a high burden and limitations to health‐related quality of life (HRQoL). Objective: The ItchyQoL was developed to assess the impairment to HRQoL in patients with CP. However, it has only been validated in English and German. Here, we report the validation in several languages across Europe. Methods: After professional translation, the versions of ItchyQoL were digitized for use as a tablet application. Validation was performed in clinics for dermatology in Austria, France, Germany, Italy, Poland, Russia, Spain, Switzerland and Turkey. Results: Five hundred and thirty‐five patients with either contact dermatitis, chronic prurigo – nodular type, psoriasis vulgaris, lichen planus or mycosis fungoides/Sézary syndrome and with CP ≥ 3 on the numerical rating scale were included. ItchyQoL showed a high level of consistency (Cronbach's‐α, all: 0.95) and test‐retest reliability (intraclass correlation: 0.91). It strongly correlated with the Dermatology Life Quality Index ( r = 0.72, P < 0.001) and moderately correlated with itch intensity scales in the study population (visual analogue scale r = 0.46; numerical rating scale r = 0.51; verbal rating scale r = 0.51, for all: P < 0.001). Conclusion: ItchyQoL is now also validated in French, Italian, Polish, Russian, Spanish and Turkish and can be used in clinical trials in countries speaking these languages.